Robotic rectal cancer surgery: comparative study of the impact of obesity on early outcomes. Issue 12 (30th September 2020) - Peacock, O.; Limvorapitak, T.; Hu, C.‐Y.; Bednarski, B. K.; Tillman, M. M.; Kaur, H.; Taggart, M. W.; Dasari, A.; Holliday, E. B.; You, Y. N.; Chang, G. J.
Abstract : The aim of this study was to compare the outcomes of robotic total mesorectal excision (TME) in obese versus non‐obese patients. A total of 533 patients, of whom 161 were obese (30·2 per cent) underwent robotic proctectomy during the study interval. Patient obesity was not associated with adverse short‐term clinical outcomes after robotic rectal cancer surgery. Indicated in the obese perhaps?